Lithium-ion Batteries Thin Film for Energy Materials and Devices - Sato, Mitsunobu; Lu, Li (InTechOpen, 2020)
The book "Lithium-ion Batteries - Thin Film for Energy Materials and Devices" provides recent research and trends for thin film materials relevant to energy utilization. The book has seven chapters with high quality content covering general aspects of the fabrication method for cathode, anode, and solid electrolyte materials and their thin films. All the chapters have been written by experts from different backgrounds, and the book is the result of collaborations between all contributing authors who agreed to share their research expertise and technological visions for the future. We hope this book will significantly stimulate readers to develop new devices.